Food Feeding and Your Family: Participant Perspectives on the Integration of Parent Feeding Behaviors Content in EFNEP Lessons. (29th May 2020) - Aragon, M Catalina; Baker, Susan; Auld, Garry; Barale, Karen; Berger, Theresa; Garcia, Karina Silva; Lanigan, Jane; Micheli, Nilda; Parker, Louise; Power, Thomas; Hughes, Sheryl
Abstract: Objectives: Determine participant's 1. perspectives on parent feeding behavior content; and 2. self-reported behavior changes. Methods: Food Feeding and Your Family (FFYF) randomized control trial with 3 arms, each with English and Spanish classes for parents with children 2–8 years old: Control, In-class, Online. Participants of the Expanded Food and Nutrition Education Program (EFNEP) received 9 lessons using the Eating Smart Being Active curriculum. In-class participants watched videos (adapted from previous work) and participated in educator led activities on parent feeding behaviors. Between lessons, Online participants received texts with links to 7 videos and activities but no in-class content. Quantitative evaluations occurred at Pre, Post, 6 and 12 months post. Telephone focus groups (FG) with participants after 12 month evaluation; 2 FG per cell (English/Spanish) x (Online/In class). Results: Participants (P) (540 enrolled in FFYF; 38 in FG) found the videos, activities, and handouts to be informative and useful. Many reported doing the activities with their children and retained handouts for review. A few English P liked the information but thought the videos were boring/childish or were less appropriate for older children. Multiple P in each FG reported behavior changes tied to parent feeding behavior topics, particularly, modifying children's portions, using strategies when introducing new foods to child (letting them "play" with the food and/or help with preparation; exposing child to food numerous times), using tips for shopping with child (feeding him first; letting her help choose healthy items), and establishing mealtime routines. Conclusions: At 12 months post program, participants recalled multiple themes related to parent feeding behaviors and valued the information. They reported numerous behavior changes made and sustained as a result of program participation. Results suggest the addition of parent –child feeding information to EFNEP lessons would be well-received and effective. Funding Sources: This research is supported by funds from the United States Department of Agriculture (Grant USDA 2015–68, 001-23, 311). The contents of this publication do not necessarily reflect the views or policies of the USDA, nor does mention of trade names, commercial products, or organizations imply endorsement from the US government.